2011
DOI: 10.5588/ijtld.10.0491
|View full text |Cite
|
Sign up to set email alerts
|

The impact of combined pulmonary fibrosis and emphysema on mortality

Abstract: CPFE is not rare and CPFE patients had a higher overall mortality risk than emphysema-only patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
26
1
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 0 publications
2
26
1
1
Order By: Relevance
“…11 Among these patients, high mean pulmonary arterial pressure, high pulmonary vascular resistance, high heart rate and low diffusing capacity for carbon monoxide (DLco) were significantly associated with poor outcome. In one study, CPFE patients had a fivefold higher mortality risk (adjusted HR 5.10, 95% CI 1.75 to 14.9) in non-malignant situations 19. In the present study, only 12 of 93 patients had lung cancer in contrast to the number reported in a previous study 10.…”
Section: Discussioncontrasting
confidence: 77%
“…11 Among these patients, high mean pulmonary arterial pressure, high pulmonary vascular resistance, high heart rate and low diffusing capacity for carbon monoxide (DLco) were significantly associated with poor outcome. In one study, CPFE patients had a fivefold higher mortality risk (adjusted HR 5.10, 95% CI 1.75 to 14.9) in non-malignant situations 19. In the present study, only 12 of 93 patients had lung cancer in contrast to the number reported in a previous study 10.…”
Section: Discussioncontrasting
confidence: 77%
“…As they were found in our SSc patients at the time of diagnosis, interstitial fibrosis with diffuse pulmonary cystic lesions may be a not so uncommon manifestation of interstitial lung disease that requires specific investigations in order to exclude infections and cancer . Our cases strengthen the hypothesis of Cottin et al .…”
supporting
confidence: 87%
“…CPFE is characterized by a relatively well-preserved lung volume, severely impaired carbon monoxide transfer, significant decrease in PaO 2 on exercise, and a high prevalence of pulmonary hypertension leading to a poor prognosis [3, 4]. We expect that the extent of pulmonary fibrosis in CPFE patients might influence the outcome, because patients with CPFE have a worse prognosis than patients with emphysema [5]. However, it is difficult to evaluate the extent of pulmonary fibrosis in patients with CPFE.…”
Section: Introductionmentioning
confidence: 99%